Enhancing delivery of information technology projects through stakeholder sense-making. (15th February 2021) - Ominde, Diana; Ochieng, Edward; Omwenga, Vincent
The aim of this paper was to examine the applicability of sense-making concepts within the context of stakeholder management in ICT projects in Kenya. The researchers adopted a qualitative approach that triangulates action research design, case-study and grounded theory. A total of 12 senior project management practitioners were identified through non-probability sampling. Conversational semi-structured interviews were carried out, responses were collated and analysed through the NVivo qualitative data analysis framework. It was found that existing stakeholder management and sense-making concepts in ICT project delivery contributes to the accurate identification of stakeholders in ICT projects. It was further found that conceptualisation encourages stakeholder engagement in ICT projects, and enhances the understanding of stakeholder roles in the projects and improves public commitment to stances that are aligned with proffered stakeholders.